The lexicon referred to young people and youth in spanish language - Reyes Núñez, Juan Pablo (Última Década, 2019)
In order to establish the features of the social imaginary regarding young individual, the present article proposes a method of interdisciplinary analysis of sociopolitical nicknames of the Spanish language related to young people and youth, through a historical and semantic analysis.